Developing a Causal Model of Marital Relationship Quality Based on Dark Personality Traits and Communication Beliefs with the Mediating Role of Emotion Regulation in Women - Enfeal , Navid; Sohrabi, Nadereh; Zarnaghash , Maryam; Sahami , Sousan (KMAN Counseling & Psychology Nexus, 2026)
The primary objective of the present study was to examine marital relationship quality based on dark personality traits and communication beliefs, considering the mediating role of emotion regulation in women. The research method was correlational with a structural equation modeling approach. The statistical population consisted of all women referring to counseling centers in the city of Shiraz in 2023. A sample of 250 participants was selected using cluster random sampling. The research instruments included the Marital Relationship Quality Questionnaire by Busby et al. (1995), the Dark Personality Traits Questionnaire by Johnson and Webster (2010), the Communication Beliefs Questionnaire by Epstein and Eidelson (1990), and the Emotion Regulation Questionnaire by Gross and John (2003). Data were analyzed using SPSS version 23 and SmartPLS version 4. The results of the structural equation model indicated that emotion regulation plays a mediating role in the relationship between marital relationship quality and both dark personality traits and communication beliefs. The proposed model can be applied as an educational intervention package to enhance couple relationships in counseling clinics.